Application of bci technology for color prediction using brainwaves - Angelovski, Martin; Lameski, Petre; Zdravevski, Eftim; Kulakov, Andrea (My University, 2012)
In this paper we present the results of the research regarding color recognition using brain-waves read from a consumer grade non-intrusive Brain Computer Interface device. The brainwaves obtained from the device are preprocessed and filtered using different algorithms and then several machine learning techniques are applied for prediction of three colors. At the end, the obtained results are presented and discussed.
Keywords: brain computer interface, brainwaves, color prediction